Peter The Great's Foreign Policy in the Assessments of Russian Conservatives of the 19th Century - E. V. Linkova (Vestnik MGIMO-Universiteta)
The article reconstructs the views of Russian conservatives on the Russia’s international position and foreign policy under Peter I. His military victories, and successes in diplomatic field made him popular among conservatives of the 19th century: N. Karamzin, F. Tutchev, M. Pogodin, S. Tatishchev, V. Lamansky, etc. In their studies they focused on Russia’s international posture in the late 17th– early 18th century, comparing the main features of Peter's diplomacy with his those of his descendants. The conservatives, while criticizing the emperor for undermining the tradition, imitating the West, and widening the socio-cultural rift in the society, highly appraised Peter’s foreign policy. They attributed the success to the foreign policy strategy based on national interests. This strategy and Peter’s personality fared better compared to the times of «palace coups», and personalities of Catherine II, Alexander I, and Nicholas I. Peter I «in his relations with foreign powers...was guided solely by the consciousness of our national benefits and needs, while strictly protecting the honor and dignity of the sovereign and the state». The conservatives criticized the emperor's 19th century heirs for what they saw as abandonment of national interests in favor of pan-European ones.